Descripción de nidos nuevos o poco conocidos de la avifauna argentina - de la Peña, Martín R. (1996)
The nests of Myiopagis caniceps, Elaenia strepera, Euphonia chlorotica and Phrygius carbonarius are deseribed; that of Myiopagis caniceps was previously unknown. I provide information on date, location, materials, shape and size of the nests, as well as on color and measurements of the eggs.